Conflitos, hegemonia e blocos no poder: a atuação das elites políticas nordestinas e suas configurações na sociedade civil a partir da transposição do rio São Francisco (2003-2008) - Duarte, Gregório Henrique Silva (Universidade Federal de São Carlos, 2024)
The research presented here aims to analyze the actions of northeastern political elites in the context of the transposition of the São Francisco River and its configurations in civil society, in order to investigate the political, economic and social developments of the work based on the movement and actions of political elites. .Issues such as the current drought industry, water conflict, political oligarchies and familism emerge as central themes of our proposal. Methodologically anchored in the perspective of conflict theory, we seek, using the analytical categories: conflicts; hegemonies; and blocks in power, investigate conflicts in the semiarid northeastern region based on the implementation of the PISF. Our research proposal is qualitative in nature, as it seeks to qualitatively approach the delimited phenomenon as an object of study. The chapters are organized into three sections, ranging from the search for a theory of elites that helps us achieve the objectives outlined in the research, going through the historical path of the relationship between political elites and droughts, to the analysis of the PISF.
Conflicts, hegemony and power blocks: the actions of northeastern political elites and their configurations in civil society after the crossing of the São Francisco River (2003-2008)
Keywords: Political elites; Elites politicas; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO